Viability and Adhesion of Periodontal Ligament Fibroblasts on a Hydroxyapatite Scaffold Combined with Collagen, Polylactic Acid-Polyglycolic Acid Copolymer and Platelet-Rich Fibrin: A Preclinical Pilot Study - Leonor C. Espitia-Quiroz; Andrés L. Fernández-Orjuela; Lina M. Anaya-Sampayo; Adriana P. Acosta-Gómez; Luis Gonzalo Sequeda-Castañeda; Sandra Janeth Gutiérrez-Prieto; Nelly S. Roa-Molina; Dabeiba A. García-Robayo (MDPI AG, 2022)
Background: Conventional periodontal therapy relies on bone regeneration strategies utilizing scaffolds made of diverse materials, among which collagen, to promote cell adhesion and growth. Objective: To evaluate periodontal ligament fibroblast (HPdLF) cell adhesion and viability for periodontal regeneration purposes on hydroxyapatite scaffolds containing collagen (HAp-egg shell) combined with polylactic acid-polyglycolic acid copolymer (PLGA) and Platelet-Rich Fibrin (PRF). Methods: Four variations of the HAp-egg shell were used to seed HPdLF for 24 h and evaluate cell viability through a live/dead assay: (1) (HAp-egg shell/PLGA), (2) (HAp-egg shell/PLGA + collagen), (3) (HAp-egg shell/PLGA + PRF) and (4) (HAp-egg shell/PLGA + PRF + collagen). Cell adhesion and viability were determined using confocal microscopy and quantified using central tendency and dispersion measurements; significant differences were determined using ANOVA (p < 0.05). Results: Group 1 presented low cell viability and adhesion (3.70-10.17%); groups 2 and 3 presented high cell viability and low cell adhesion (group 2, 59.2-11.1%, group 3, 58-4.6%); group 4 presented the highest cell viability (82.8%) and moderate cell adhesion (45%) (p = 0.474). Conclusions: The effect of collagen on the HAp-egg shell/PLGA scaffold combined with PRF favored HPdLF cell adhesion and viability and could clinically have a positive effect on bone defect resolution and the regeneration of periodontal ligament tissue.